Application of the Chinese Version of the BIS/BAS Scales in Participants With a Substance Use Disorder: An Analysis of Psychometric Properties and Comparison With Community Residents - Che, Qingqing; Yang, Peiwen; Gao, Huiyuan; Liu, Meizhu; Zhang, Jun; Cai, Taisheng (Frontiers in Psychology, 2020)
Carver and White developed the Behavioral Inhibition/Behavioral Activation Scales (the BIS/BAS Scales) based on Reinforcement Sensitivity Theory proposed by Gray. Subsequent studies proposed that substance abuse was closely related to Behavioral Inhibition System (BIS) and Behavioral Activation System (BAS). However, researches on the psychometric properties of the BIS/BAS scales in clinical samples are scarce. The present study was conducted to analyze the applicability of the BIS/BAS scales in a sample suffering from a substance use disorder (SUD) and undergoing treatment in compulsory detoxification institutions (n = 1117). Meanwhile, 822 community residents were selected for comparison. Confirmatory factor analysis was carried out to examine the construct validity and the results showed that the five-factor model was the best fit for people with a substance use disorder’ data. Besides, Cronbach’s alpha coefficient for the total scale was 0.808, indicating the satisfactory internal consistency reliability. Analysis of the correlation coefficient of the questionnaire with the corresponding personality traits showed that BAS was more associated with the impulsive trait. Surprisingly, participants with a substance use disorder showed more insensitivity for the reward dimension compared with that of community residents and the result of comparison between two samples supported joint subsystems hypothesis. Generally, the BIS/BAS scales showed good reliability and validity. These findings provide more direct evidence on the personality traits of people with a substance use disorder and should form the basis for further research.